The Effectiveness of Generalis Murotal Therapy on Mr. K with Sensory Perception Disorders and Auditory Hallucinations at Wisma Lily 9, Soerojo Hospital, Magelang - Maulana Ajis, Idwan; Sari Purbaningsih, Endah; Fadila, Erida (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Schizophrenia is a persistent and serious neurobiological brain disorder, a clinical syndrome that can cause damage to the lives of individuals, families, and communities. One of its symptoms is that a person with schizophrenia will experience auditory hallucinations. Hallucinations are false perceptual distortions resulting from maladaptive neurobiological responses. The client actually experiences sensory distortions but perceives them as real. To address hallucinations, two techniques can be employed: pharmacological and non-pharmacological. Pharmacological techniques involve collaborating with a doctor to administer medication such as Haloperidol, Serenace, Lodomer, or Chlorpromazine. Non-pharmacological techniques include individual therapy, biological therapy, cognitive therapy, environmental therapy, family therapy, and behavioral therapy. Method: A qualitative approach using a case study research design was employed. The subject of this study was one client with auditory hallucinations in Room Wisma Lily 9. Data collection techniques included interviews, observations, and documentation. Result: The case study results showed that the sensory perception disorder was resolved. Therefore, it can be concluded that nursing care, which includes assessment, diagnosis, intervention, implementation, and evaluation, combined with the application of video therapy, effectively reduces the level of hallucinations, frequency of hallucinations, and duration of hallucinations in schizophrenia patients. Conclusion: It is recommended that nurses continue to implement nursing interventions for patients with sensory perception disorders: auditory hallucinations effectively to improve and optimize the level of hallucinations in patients.